2021
DOI: 10.22541/au.161262483.32657582/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of Intra-Aortic Balloon Pump During Coronary Artery Bypass Graft Surgery. Current Questions and Few Answers.

Abstract: The intra-aortic balloon pump (IABP) is used to prevent complications after coronary artery bypass grafting (CABG) surgery; although some results are controversial nowadays even contradictory. A new article on this field is published in this edition and shows that the risk factors for in-hospital mortality are the preoperative plasma creatinine level and cardiopulmonary bypass time in 177 patients. About the prophylactic use of the IABP regarding mortality the results reflected so far in meta-analyses have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…IABP use in various operations has continued to vary as a result of the lack of supporting data. [19] The majority of studies have shown a promising survival benefit for CAD patients receiving surgical therapy. However, it is claimed that low cardiac output syndrome as well as mortality in CABG are predicted by significant LV dysfunction (ejection fraction 35%) [20].…”
Section: Use Of Iapb During (Cabg) Surgerymentioning
confidence: 99%
“…IABP use in various operations has continued to vary as a result of the lack of supporting data. [19] The majority of studies have shown a promising survival benefit for CAD patients receiving surgical therapy. However, it is claimed that low cardiac output syndrome as well as mortality in CABG are predicted by significant LV dysfunction (ejection fraction 35%) [20].…”
Section: Use Of Iapb During (Cabg) Surgerymentioning
confidence: 99%